The Future of the Public Policy School in a World of Disruptive Innovation. Issue 1 (27th February 2019) - Anderson, Lisa
Abstract : At the same time, as we embrace innovation, and confront disrupting our comfortable "standard operating procedures, " to use another cornerstone of our curricula, we must always hold fast to the principle that the rule of law is essential to effective governance and the flourishing of society.